2017
DOI: 10.1089/neu.2016.4536
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function and Associated Clinical Correlates in Former National Football League Players

Abstract: Professional American football players incur thousands of repetitive head impacts (RHIs) throughout their lifetime. The long-term consequences of RHI are not well characterized, but may include olfactory dysfunction. RHI has been associated with changes to brain regions involved in olfaction, and olfactory impairment is common after traumatic brain injury. Olfactory dysfunction is a frequent early sequelae of neurodegenerative diseases (e.g., Alzheimer's disease), and RHI is associated with the neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 78 publications
0
68
0
Order By: Relevance
“…Participants also completed standardized self-report and semi-structured interviews to assess behaviour and mood symptoms, including depression, suicidality, hopelessness, apathy, aggression, impulsivity, and hostility. A complete list of neuropsychological tests and measures of behaviour and mood have been reported elsewhere [32]. As described previously [32], Principal Component Analysis (PCA) generated four factors from the neuropsychological and behaviour/mood measures and included: Behavioural/mood, Psychomotor Speed/Executive Function, Verbal Memory, and Visual Memory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also completed standardized self-report and semi-structured interviews to assess behaviour and mood symptoms, including depression, suicidality, hopelessness, apathy, aggression, impulsivity, and hostility. A complete list of neuropsychological tests and measures of behaviour and mood have been reported elsewhere [32]. As described previously [32], Principal Component Analysis (PCA) generated four factors from the neuropsychological and behaviour/mood measures and included: Behavioural/mood, Psychomotor Speed/Executive Function, Verbal Memory, and Visual Memory.…”
Section: Methodsmentioning
confidence: 99%
“…A complete list of neuropsychological tests and measures of behaviour and mood have been reported elsewhere [32]. As described previously [32], Principal Component Analysis (PCA) generated four factors from the neuropsychological and behaviour/mood measures and included: Behavioural/mood, Psychomotor Speed/Executive Function, Verbal Memory, and Visual Memory. PCA was performed to minimize the number of analyses and reduce type I error risk.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies 15,32,35,46,52,55 used subjective (self-reported) cognitive tests alone. The re-* References 14,19,21,23,24,27,28,30,34,36,37,39,41,43,44,47,[49][50][51]55. †References 16,18,20,25,35,40,42,45,46,48,52 (Figure 3). Memory was the most commonly studied cognitive health outcome (n ¼ 31, 67%), followed by attention (n ¼ 17, 37%) and global cognitive ability (n ¼ 16, 35%).…”
Section: Types Of Outcome Measures Usedmentioning
confidence: 99%
“…Tests of attention were administered in 17 (37%) of 46 investigations. † † In 3 studies, 23,28,31 investi- Table 2). The authors of 14 (45%) studies § § reported normal functioning on memory tests.…”
Section: Cognitive Findingsmentioning
confidence: 99%
See 1 more Smart Citation